Directions of increasing innovativeness of economy: The case of Poland - Olga Okrzesik (Economic and Environmental Studies (E&ES), 2018)
Innovations significantly affect a country's economic development, at the same time contributing to raising its position. A very important role in improving the innovativeness of enterprises, regions or the national economy is played by the state, creating a strategy, programmes or regulations supporting development and pro-innovation policy. This article attempts to systematise knowledge in the field of innovation and to determine directions for increasing the innovativeness of the economy in Poland. This study analyses strategies supporting innovation in Poland in the years 2014-2020.
Keywords: L10; L22; O10; O31; 330; development strategies; innovativeness; enterprises